2012
DOI: 10.1186/1423-0127-19-28
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between osteoclastogenic and anti-osteoclastogenic pro-inflammatory cytokines differs in human osteoporotic and osteoarthritic bone tissues

Abstract: BackgroundPro-inflammatory cytokines possess osteoclastogenic or anti-osteoclastogenic activities. They influence osteoclasts directly or via the receptor activator of nuclear factor κB (RANK), RANK ligand (RANKL) and osteoprotegerin (OPG) system. Recent evidence suggests that inflammation may play a role in osteoporosis (OP) and osteoarthritis (OA). We aimed therefore to determine whether there is a difference between both groups: first, in the expression of the osteoclastogenic and anti-osteoclastogenic cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 38 publications
1
42
0
3
Order By: Relevance
“…Among these common DEGs, the upregulated genes MDK (Weckbach et al, 2012) and HLA-DMB (Morel et al, 2004) and the down-regulated genes FABP4 (Andres Cerezo et al, 2013) and BCL6 (Baecklund et al, 2006) have been previously reported to be associated with RA, whereas there is no definite conclusion about the roles of genes TNFRSF11A, RGS19, ADCY1, TRIM14, TK1, APOBEC3G, ITPKC, AMPH, DDIT4, MIR1908, APOD, SFPQ and CITED1 in RA pathogenesis. Similarly, the up-regulated gene TNFRSF11A (Zupan et al, 2012) and down-regulated gene APOD (Tew et al, 2007) have also been regarded as important mediators in OA, whereas there is no explicit conclusion about the roles of genes RGS19, MDK, ADCY1, TRIM14, HLA-DMB, TK1, APOBEC3G, ITPKC, AMPH, DDIT4, MIR1908, FABP4, SFPQ, CITED1 and BCL6 in the OA pathogenesis. PPI network analysis of the commonly changed genes of OA and RA demonstrates that only genes CXCL12, MMP-1, PPARG and FABP4 constitute lineinteraction, indicating that these genes may form a gene signature of RA and OA and highlighting the importance of further investigating the functional interplay of this gene signature in the pathogenesis of RA and OA.…”
Section: Discussionmentioning
confidence: 96%
“…Among these common DEGs, the upregulated genes MDK (Weckbach et al, 2012) and HLA-DMB (Morel et al, 2004) and the down-regulated genes FABP4 (Andres Cerezo et al, 2013) and BCL6 (Baecklund et al, 2006) have been previously reported to be associated with RA, whereas there is no definite conclusion about the roles of genes TNFRSF11A, RGS19, ADCY1, TRIM14, TK1, APOBEC3G, ITPKC, AMPH, DDIT4, MIR1908, APOD, SFPQ and CITED1 in RA pathogenesis. Similarly, the up-regulated gene TNFRSF11A (Zupan et al, 2012) and down-regulated gene APOD (Tew et al, 2007) have also been regarded as important mediators in OA, whereas there is no explicit conclusion about the roles of genes RGS19, MDK, ADCY1, TRIM14, HLA-DMB, TK1, APOBEC3G, ITPKC, AMPH, DDIT4, MIR1908, FABP4, SFPQ, CITED1 and BCL6 in the OA pathogenesis. PPI network analysis of the commonly changed genes of OA and RA demonstrates that only genes CXCL12, MMP-1, PPARG and FABP4 constitute lineinteraction, indicating that these genes may form a gene signature of RA and OA and highlighting the importance of further investigating the functional interplay of this gene signature in the pathogenesis of RA and OA.…”
Section: Discussionmentioning
confidence: 96%
“…Three major causative factors are actually recognized: calcium malabsorption, corticosteroid treatment, and inflammation (Bianchi, 2010;Card et al, 2004). More and more results emphasize the role of inflammation (Moschen et al, 2005;Zupan et al, 2012;Agrawal et al, 2011). Because the AOPPs are displayed as pro-inflammatory cytokines in IBD, we expected to identify their accumulation as a new candidate mechanism for IBD-associated bone loss.…”
Section: Discussionmentioning
confidence: 97%
“…Because the accumulative concentration of plasma AOPPs are closely correlated with the level of dityrosine (a hallmark of oxidized protein), the AOPPs have been considered as a novel marker of oxidant-mediated protein damage (Witko-Sarsat et al, 1996, 1998. Increased levels of AOPPs, which are also closely related to the severity of disease, have recently been found in diabetes (Kalousova et al, 2002;Martin-Gallan et al, 2003;Sebekova et al, 2012), coronary artery disease (Skvarilova et al, 2005), cancer (Kosova et al, 2007;Chang et al, 2008), liver cirrhosis (Zuwala-Jagiello et al, 2011), and chronic inflammatory bowel disease (IBD) (Baskol et al, 2008;Krzystek-Korpacka et al, 2008). This implies that the accumulation of AOPPs may be relevant in mechanisms underlying numerous pathophysiologic conditions.…”
Section: Introductionmentioning
confidence: 94%
“…При цьому діляться переважно клітини фібробластичного ряду. Дефінітивні форми лейкоцитів, макрофа-гів і тучних клітин можуть проліферувати під впливом низки факторів [13][14][15]. Однак у цілому вони не схильні до поділу.…”
Section: результати та їх обговоренняunclassified